The Effect of Load-based Exercise Intensity on Testicular Malondialdehyde Concentration, Testicular Caspase-3 Expression, and Sperm Quality in Mice (Mus Musculus) - Priscilia Pratami Intan; Reny I'tishom; Vellyana Lie; Ria Margiana; Syed Baharom Syed Ahmad Fuad; Gadis Meinar Sari (Biomolecular and Health Science Journal)
Introduction: Studies over the past decades reveal the global decline of sperm quality among unselected men, particularly in its concentration. The impacts of exercise on sperm quality are still ambiguous. This study aims to analyze the effects of different exercise intensities on testicular malondialdehyde (MDA), testicular caspase-3, and sperm quality in mice. This study might result in the recommendation of exercise intensity that improves and protects sperm quality. Methods: Male Deutschland–Denken–Yoken mice were divided into four groups: a control group and three intervention groups with different loads (low, moderate, and high) based on 3%, 6%, and 9% of body weight. MDA level by ELISA and caspase-3 by immunohistochemistry were assessed from the testicles. The sperm characteristics and quality were analyzed using the WHO standards. The multivariate data were statistically analyzed using one-way analysis of variance and Kruskal–Wallis. Results: The testicular MDA level and caspase-3 expression were lower in the exercise groups than in the control group (P < 0.05). Increasing intensity increased the MDA level (P < 0.05) and expression of caspase-3 (P < 0.05), and the lowest measurements were in the low group (P < 0.05). Sperm concentration, motility, morphology, and viability were no different between groups (P > 0.05). Conclusions: Different exercise intensities have different but linear effects on testicular MDA and caspase-3. The lower exercise intensity, the lower testicular MDA and caspase-3. However, their impact on sperm quality needs more exploration.